Low heat of hydration concrete and method for making same
Patent Information
- Application Number
- CN202610927510.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-25
- Publication Date
- 2026-10-16
AI Technical Summary
然而,这种技术方案存在一个根本矛盾:自密实性能所要求的高胶凝材料总量,恰恰是导致水化热升高的主要原因
1、由于本申请采用由水泥、粉煤灰、矿粉、硅灰组成的四元胶凝体系,利用各组分水化放热速率的时间差异,使原本集中在水泥水化初期的放热峰在时间轴上错位展开,水泥的快速放热由硅灰的火山灰反应接替,矿粉的中速放热填充中间时段,粉煤灰的缓慢放热延续至后期,从而实现总放热曲线的扁平化,峰值高度显著降低。获得了在维持较高胶凝材料总量以满足自密实填充要求的前提下,有效抑制随之而来的高水化热问题的效果。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of concrete, and more specifically, to a low heat of hydration concrete and a method for preparing the same. Background Technology
[0002] Low-heat-of-hydration concrete refers to concrete whose composition of cementitious materials is adjusted to reduce the rate and total amount of heat released during cement hydration. It is widely used in large-volume concrete structures such as subway stations, dams, bridge piers, and high-rise building slabs. These projects require high crack resistance in the concrete. Excessive heat of hydration causes a rapid rise in the internal temperature of the concrete, creating a large temperature difference with the surface. When the resulting temperature stress exceeds the tensile strength of the concrete, cracks appear, affecting the structural durability and waterproofing performance. Low-heat-of-hydration concrete, with its self-compacting properties, can fill narrow spaces by its own weight without the need for vibration, making it particularly suitable for construction scenarios with dense reinforcement and difficult vibration, such as subway station side walls and underground tunnel linings.
[0003] In related technologies, to achieve self-compacting properties, concrete needs a high total amount of cementitious materials to ensure sufficient paste volume and low yield stress, thereby achieving good fluidity and filling capacity. However, this technical solution has a fundamental contradiction: the high total amount of cementitious materials required for self-compacting properties is precisely the main cause of increased heat of hydration. In other words, how to effectively suppress the resulting high heat of hydration while maintaining a high total amount of cementitious materials to meet the self-compacting filling requirements is a problem that related technologies have failed to solve. Summary of the Invention
[0004] In order to effectively suppress the high heat of hydration problem while maintaining a high total amount of cementitious material to meet the self-compacting filling requirements, this application provides a low heat of hydration concrete and its preparation method.
[0005] In a first aspect, this application provides a low-heat-of-hydration concrete, which adopts the following technical solution: A low-heat-of-hydration concrete comprises the following raw materials in parts by weight: 218-225 parts cement; 160-168 parts of fly ash; 118-125 parts of mineral powder; 23-24 parts silica fume; 820-830 parts of graded coarse aggregate; Fine aggregate 850-855 parts; 10-11 parts of slow-release polycarboxylate superplasticizer; 0.03–0.032 parts of air-entraining agent; The water-to-binder ratio is 0.3 to 0.31.
[0006] By adopting the above technical solution, a quaternary cementitious system composed of cement, fly ash, mineral powder, and silica fume is constructed. By utilizing the time difference in the hydration heat release rate of each component, the heat release peak that was originally concentrated in the early stage of cement hydration is staggered on the time axis. The rapid heat release of cement is replaced by the pozzolanic reaction of silica fume, the medium-speed heat release of mineral powder fills the middle period, and the slow heat release of fly ash continues into the later stage, thereby achieving a flattening of the total heat release curve and a significant reduction in peak height.
[0007] Existing technologies typically pursue a single performance characteristic (such as extremely low heat of hydration or ultra-high strength), often deviating from the specific requirements of self-compacting concrete for high total volume and low cement ratio. This results in either insufficient early strength, excessive paste viscosity, or loss of self-compacting properties. This solution precisely controls the cement ratio while maintaining the high total volume requirement of self-compacting concrete. Simultaneously, it blends silica fume, mineral powder, and fly ash in specific proportions, ensuring that the components "relay" rather than "overlap" on the heat release time axis. This achieves low heat of hydration without sacrificing self-compacting properties and early strength.
[0008] The slow-release water-reducing agent's release time matches the exothermic peak misalignment window of the quaternary system, further shifting the exothermic peak later. The reduced porosity of the three-graded aggregate precisely offsets the viscosity increase caused by silica fume in the quaternary system, resulting in an increase in self-compacting performance rather than a decrease. The addition of the air-entraining agent further reduces the slurry yield stress, allowing the synergistic effect of the above factors to be fully released.
[0009] By placing the aforementioned technical methods under the specific constraint of "high total amount, low cement ratio," and precisely controlling the proportioning window of each element, they are matched and amplified to each other, rather than hindering or canceling each other out. The absence or deviation of any element from the specified range will disrupt this balance, resulting in one of the following failing to meet the standards: self-compacting performance, strength, or heat of hydration. Therefore, the goal is to effectively suppress the resulting high heat of hydration while maintaining a high total amount of cementitious material to meet the self-compacting filling requirements.
[0010] Optionally, the cement is PO 42.5 ordinary Portland cement; the fly ash is Grade I fly ash; the mineral powder is S95 grade granulated blast furnace slag powder; and the silica fume is dense micro silica fume.
[0011] Optionally, the concrete may also include the following raw materials in parts by weight: Halloysite nanotubes, 8–12 parts; 12-16 parts of calcium carbonate whiskers; Polyvinyl alcohol fiber 1.5 to 2 parts.
[0012] By adopting the above technical solution, a ternary composite system of halloysite nanotubes, calcium carbonate whiskers, and polyvinyl alcohol fibers is introduced. Halloysite nanotubes (nanoscale tubular), calcium carbonate whiskers (micrometer-scale whisker-like), and polyvinyl alcohol fibers (millimeter-scale fibrous) form a "nano / micro / millimeter" multi-scale reinforcing network. The lumen of the halloysite nanotubes can store heat and buffer, adsorb free water and delay hydration, achieving an auxiliary cooling effect. Calcium carbonate whiskers do not participate in early hydration, and polyvinyl alcohol fibers do not increase the heat of hydration; together, they reduce the heat of hydration. Calcium carbonate whiskers microscopically inhibit cracking, while polyvinyl alcohol fibers macroscopically toughen, comprehensively covering the crack control needs from micro to macro. The composite of the three has a further effect of delaying hydration and synergistic reinforcement, which is superior to single fillers.
[0013] Optionally, the halloysite nanotube has paraffin loaded inside its lumen and sodium gluconate loaded on its outer wall.
[0014] By employing the above technical solution, the inner wall of the halloysite nanotube carries a positive charge, while the outer wall carries a negative charge. Paraffin (a phase change material) is encapsulated within the halloysite nanotube's cavity, while sodium gluconate (a retarder) is adsorbed onto the outer wall, creating a partitioned loading system of "inner + outer." The latent heat storage (physical cooling) of paraffin and the slow-release and retarding (chemical cooling) of sodium gluconate synergistically reduce and delay the exothermic peak. Furthermore, the partitioned loading design avoids the competitive adsorption problem of the two functional substances vying for cavity space, maximizing their respective efficiencies.
[0015] Optionally, the paraffin loading is 50% of the halloysite nanotube mass.
[0016] Optionally, the sodium gluconate loading is 5% of the mass of halloysite nanotubes.
[0017] Optionally, the method for preparing the halloysite nanotubes loaded with paraffin and sodium gluconate is as follows: The dried halloysite nanotubes were mixed with molten paraffin and kept under vacuum to allow the paraffin to enter the lumen of the halloysite nanotubes; the mixture was then filtered and separated, and excess paraffin was washed off the surface. Halloysite nanotubes loaded with paraffin are dispersed in an aqueous solution of sodium gluconate and stirred to allow sodium gluconate to be electrostatically adsorbed on the outer wall of the halloysite nanotubes. After filtration, drying, and grinding through a 200-mesh sieve, a composite powder of halloysite nanotubes loaded with paraffin and sodium gluconate is obtained.
[0018] Secondly, this application provides a method for preparing low-heat-of-hydration concrete, employing the following technical solution: A method for preparing low-heat hydration concrete includes the following steps: pretreatment of each raw material, step-by-step mixing, and mixing until homogeneous.
[0019] By adopting the above technical solution, the concrete produced can effectively suppress the high heat of hydration problem while maintaining a high total amount of cementitious material to meet the self-compacting filling requirements.
[0020] In summary, this application has the following beneficial effects: 1. Because this application employs a quaternary cementitious system composed of cement, fly ash, mineral powder, and silica fume, it utilizes the temporal differences in the hydration heat release rates of each component to shift the heat release peak, which was originally concentrated in the early stage of cement hydration, across the time axis. The rapid heat release of cement is replaced by the pozzolanic reaction of silica fume, the medium-speed heat release of mineral powder fills the middle period, and the slow heat release of fly ash continues into the later stage, thereby achieving a flattening of the overall heat release curve and a significant reduction in peak height. This achieves the effect of effectively suppressing the high heat of hydration problem while maintaining a high total amount of cementitious material to meet the self-compacting filling requirements.
[0021] 2. In this application, halloysite nanotubes are preferably used to form a "nano / micro / millimeter" multi-scale reinforcement network with calcium carbonate whiskers and polyvinyl alcohol fibers. The combination of the three has the effect of further delaying hydration and synergistic reinforcement.
[0022] 3. The method of this application produces concrete that can effectively suppress the high heat of hydration while maintaining a high total amount of cementitious material to meet the self-compacting filling requirements. Detailed Implementation
[0023] The present application will be further described in detail below with reference to the embodiments. It should be noted that: unless otherwise specified, the conditions in the following embodiments shall be performed under conventional conditions or conditions recommended by the manufacturer, and the raw materials used in the following embodiments shall be commercially available unless otherwise specified.
[0024] Slow-release polycarboxylate superplasticizer, brand: Liaoning Hengda.
[0025] Air-entraining agent, bamboo oil, AE-380.
[0026] Halloysite nanotubes, purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd., XFI50 (item number 103763).
[0027] Calcium carbonate whiskers, brand: Zhenjin, length: 30μm, model: ZJ-170.
[0028] Polyvinyl alcohol fiber, 12mm in length, spiral shape. Example Example 1
[0029] A low-heat-of-hydration concrete comprises the following raw materials by weight: 218 kg of cement; 168 kg of fly ash; 125 kg of mineral powder; 23 kg of silica fume; 830 kg of graded coarse aggregate; 850 kg of fine aggregate river sand; 11 kg of slow-release polycarboxylate superplasticizer; 0.03 kg of air-entraining agent; water-cement ratio of 0.3.
[0030] The cement is PO 42.5 ordinary Portland cement; the fly ash is Grade I fly ash; the mineral powder is S95 grade granulated blast furnace slag powder; the silica fume is densely packed microsilica fume. The coarse aggregate is crushed stone, three-graded, with a weight ratio of small stone: medium stone: large stone of 3:3:4. The fine aggregate is river sand with a fineness modulus of 2.8.
[0031] A method for preparing low-heat-of-hydration concrete includes the following steps: Pretreatment of raw materials: Mix silica fume with some water and stir at 800 rpm for 2 minutes using a high-speed disperser to prepare silica fume suspension; Dissolve slow-release polycarboxylate superplasticizer and air-entraining agent in some water to prepare admixture solution; Mix in stages until homogeneous: Dry mix cement, fly ash, and mineral powder until homogeneous; add coarse and fine aggregates and continue dry mixing until homogeneous; add the remaining water and continue mixing until homogeneous; slowly add admixture solution and silica fume suspension and continue mixing until the concrete is homogeneous. Example 2
[0032] The difference between this embodiment and Embodiment 1 is that the amount of each raw material used is different.
[0033] A low-heat-of-hydration concrete comprises the following raw materials by weight: 220 kg of cement; 165 kg of fly ash; 120 kg of mineral powder; 23.5 kg of silica fume; 820 kg of graded coarse aggregate; 855 kg of fine aggregate river sand; 10.5 kg of slow-release polycarboxylate superplasticizer; 0.032 kg of air-entraining agent and triterpenoid saponins; water-cement ratio of 0.306. Example 3
[0034] The difference between this embodiment and Embodiment 1 is that the amount of each raw material used is different.
[0035] A low-heat-of-hydration concrete comprises the following raw materials by weight: 225 kg of cement; 160 kg of fly ash; 118 kg of mineral powder; 24 kg of silica fume; 820 kg of graded coarse aggregate; 855 kg of fine aggregate river sand; 10 kg of slow-release polycarboxylate superplasticizer; 0.032 kg of air-entraining agent and triterpenoid saponins; water-cement ratio of 0.309. Example 4
[0036] The difference between this embodiment and Embodiment 2 is that the concrete also includes the following raw materials: Halloysite nanotubes 8kg; calcium carbonate whiskers 16kg; polyvinyl alcohol fiber 1.5kg.
[0037] A method for preparing low-heat-of-hydration concrete includes the following steps: Pretreatment of raw materials: Mix silica fume with some water and stir at 800 rpm for 2 minutes using a high-speed disperser to prepare silica fume suspension; Dissolve slow-release polycarboxylate superplasticizer and air-entraining agent in some water to prepare admixture solution; Soak polyvinyl alcohol fiber in water for 3 hours to fully swell it, drain off excess water and set aside; Mix halloysite nanotubes and calcium carbonate whiskers evenly in advance. Mix in stages until homogeneous: Dry mix cement, fly ash, mineral powder, halloysite nanotubes and calcium carbonate whiskers until homogeneous; add coarse aggregate, fine aggregate and soaked polyvinyl alcohol fiber and continue to dry mix until homogeneous; add the remaining water and continue to stir until homogeneous; slowly add admixture solution and silica fume suspension and continue to stir until the concrete is homogeneous. Example 5
[0038] The difference between this embodiment and Embodiment 4 is that the following raw materials are used in the concrete: Halloysite nanotubes 10kg; calcium carbonate whiskers 15kg; polyvinyl alcohol fiber 1.8kg. Example 6
[0039] The difference between this embodiment and Embodiment 4 is that the following raw materials are used in the concrete: Halloysite nanotubes 12kg; calcium carbonate whiskers 12kg; polyvinyl alcohol fiber 2kg. Example 7
[0040] The difference between this embodiment and Embodiment 5 is that there are no halloysite nanotubes in the concrete. Example 8
[0041] The difference between this embodiment and Embodiment 5 is that there are no calcium carbonate whiskers in the concrete. Example 9
[0042] The difference between this embodiment and Embodiment 5 is that there are no polyvinyl alcohol fibers in the concrete. Example 10
[0043] The difference between this embodiment and Embodiment 5 is that the halloysite nanotube has paraffin loaded inside the tube cavity and sodium gluconate loaded on the outer wall of the tube.
[0044] The paraffin loading was 50% of the halloysite nanotube mass, and the phase transition temperature was 40–60 °C; the sodium gluconate loading was 5% of the halloysite nanotube mass.
[0045] The preparation method of halloysite nanotubes loaded with paraffin and sodium gluconate is as follows: Halloysite nanotubes dried at 110℃ for 3 hours were mixed with completely molten paraffin at a mass ratio of 1:1. The mixture was kept under a vacuum of ≤-0.095 MPa for 45 minutes, allowing the paraffin to enter the cavity of the halloysite nanotubes under negative pressure. The mixture was then filtered, and excess paraffin was washed off the surface with anhydrous ethanol. The paraffin-loaded halloysite nanotubes were dispersed in a 5% (w / w) sodium gluconate aqueous solution and stirred, allowing sodium gluconate to be electrostatically adsorbed onto the outer wall of the halloysite nanotubes. The mixture was then filtered, dried at 50℃, and ground through a 200-mesh sieve to obtain the halloysite nanotube composite powder loaded with paraffin and sodium gluconate. Example 11
[0046] The difference between this embodiment and Embodiment 10 is that the halloysite nanotubes are not loaded with sodium gluconate. Example 12
[0047] The difference between this embodiment and Embodiment 10 is that the halloysite nanotubes are not loaded with paraffin. Example 13
[0048] The difference between this embodiment and Embodiment 10 is that the loading is not partitioned. The loading method is as follows: halloysite nanotubes dried at 110℃ for 3 hours, completely melted paraffin, and a saturated sodium gluconate solution are mixed and kept under vacuum of ≤-0.095MPa for 60 minutes to allow the paraffin and sodium gluconate to be adsorbed into the halloysite nanotubes. After filtration and separation, the mixture is dried at 50℃ and ground through a 200-mesh sieve to obtain halloysite nanotube composite powder loaded with paraffin and sodium gluconate.
[0049] The preparation results showed that the loading amount did not meet the requirements, and the paraffin and sodium gluconate competed for space inside the tube, making it impossible to obtain powder with uniform properties. Comparative Example
[0050] Comparative Example 1 The difference between this comparative example and Example 2 is that the cement is 350 kg, fly ash is 100 kg, mineral powder is 80 kg, there is no silica fume, and the water-cement ratio is 0.33.
[0051] Comparative Example 2 The difference between this comparative example and Example 2 is that 250 kg of fly ash, 60 kg of mineral powder, no silica fume, and a water-cement ratio of 0.32 are used.
[0052] Comparative Example 3 The difference between this comparative example and Example 2 is that there is no silica fume, and the fly ash content is 175 kg and the mineral powder content is 125 kg. Performance testing Detection methods
[0053] Referring to GB / T 50080-2016 "Standard for Test Methods of Performance of Ordinary Concrete Mixtures", samples of concrete prepared in the above embodiments and comparative examples were taken and slump expansion, air content and adiabatic temperature rise were determined. The test results are detailed in Table 1.
[0054] Referring to GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", samples of concrete prepared in the above embodiments and comparative examples were taken, and the specimens were cured to the specified age according to the standard method for self-compacting concrete. The compressive strength was then determined, and the test results are detailed in Table 1.
[0055] Table 1 Test Results
[0056] Combining Examples 1, 2, and 3 with Table 1, it can be seen that under the constraint of maintaining a high total amount of cementitious materials, as the cement content increased from 40.8% (Example 1) to 42.7% (Example 3), the 28-day compressive strength increased from 63.2 MPa to 65.0 MPa, but the peak adiabatic temperature rise increased from 43.6℃ to 44.2℃, and the time of the temperature peak appeared earlier from 71 hours to 63 hours. This indicates that precise control of the cement content is the key variable for achieving a balance between "high strength and low heat of hydration". Example 2 (cement content 41.6%) achieved the optimal balance between strength, temperature rise, and spread, verifying the design principle of "heat release time misalignment" in the quaternary cementitious system.
[0057] Combining Example 2 and Comparative Example 1 with Table 1, it can be seen that Comparative Example 1, by increasing the cement content and eliminating the synergistic combination of mineral admixtures, exhibited a significantly higher adiabatic temperature rise, far exceeding the low hydration heat control target. This indicates that while simply increasing the cement content can achieve higher early strength, it exacerbates the concentrated release of hydration heat and fails to solve the high temperature rise problem caused by the high total amount of cementitious materials in self-compacting concrete. This verifies the necessity of the core design concept of this invention, "reducing the cement content with a quaternary cementitious system."
[0058] Combining Example 2 and Comparative Example 2 with Table 1, it can be seen that: Comparative Example 2, which uses a large amount of fly ash to replace cement, effectively reduces the heat of hydration, but its spreadability drops significantly to a level that does not meet the self-compacting performance requirements, and its early strength is significantly reduced. This indicates that simply relying on increasing the fly ash content to reduce the heat of hydration will lead to excessively high slurry viscosity and loss of fluidity, while the insufficient cement content will prevent the early strength from meeting the requirements. In contrast, Example 2, through the synergistic substitution of fly ash, mineral powder, and silica fume, achieves a balance between low heat of hydration and self-compacting performance while maintaining the total amount of cementitious materials unchanged.
[0059] Combining Example 2 and Comparative Example 3 with Table 1, it can be seen that in Comparative Example 3, the early strength decreased significantly after silica fume was removed. This indicates that silica fume plays an irreplaceable role in "early strength compensation" in the quaternary cementitious system. Without silica fume, even with the same total amount of cementitious materials and cement ratio, the early strength cannot meet the construction requirements for C50 grade.
[0060] Combining Examples 2 and 5 with Table 1, it can be seen that Example 5, based on Example 2, introduces a ternary composite system of halloysite nanotubes, calcium carbonate whiskers, and polyvinyl alcohol fibers. This significantly improves the mechanical properties, delays the peak temperature appearance time, and significantly reduces the segregation rate. While the slump spread decreases slightly, it still meets the self-compacting performance requirements. This demonstrates that the ternary composite system effectively enhances the mechanical properties and temperature control capabilities of concrete without compromising its self-compacting performance, verifying the effectiveness of the "nano / micro / millimeter" multi-scale reinforcement network.
[0061] Combining Examples 5 with Examples 7, 8, and 9, and referring to Table 1, it can be seen that the peak temperature appearance times of Examples 7 (lacking halloysite nanotubes), 8 (lacking calcium carbonate whiskers), and 9 (lacking polyvinyl alcohol fibers) are all significantly earlier than that of Example 5 (fully compounded), and the segregation rates are all higher than those of Example 5. When any one of the three materials is missing, the peak temperature delay effect is extremely limited, and the segregation rate cannot be reduced to the level of Example 5; when all three are present, the peak temperature appearance time is significantly improved, and the segregation rate is reduced to the optimal level. This "threshold breakthrough" phenomenon proves that halloysite nanotubes (nanoscale tubular), calcium carbonate whiskers (micrometer-scale whisker-like), and polyvinyl alcohol fibers (millimeter-scale fibrous) are not simply a functional superposition, but form a complete "nano / micro / millimeter" three-dimensional multi-scale network. The nanoscale HNTs fill the micropores and provide heat storage in the cavity, the micrometer-scale whiskers bridge microcracks and block heat conduction channels, and the millimeter-scale PVA fibers macroscopically toughen and constrain slurry flow. The three are complementary in scale and synergistic in function, and none of them can be missing. The absence of any link will lead to the collapse of the three-dimensional network.
[0062] Combining Examples 5 and 10 with Table 1, it can be seen that Example 10, based on Example 5, upgrades halloysite nanotubes to a partitioned loaded composite powder consisting of "paraffin loaded inside the tube + sodium gluconate loaded outside the tube." This further reduces the adiabatic temperature rise, significantly delays the peak temperature appearance time, and slightly improves the mechanical properties. This indicates that the latent heat storage (physical cooling) of paraffin and the slow-release and slow-condensation (chemical cooling) of sodium gluconate produce a synergistic effect under the "inside + outside" partitioned loading structure of the halloysite nanotubes, further enhancing the temperature control effect based on the multi-scale reinforcement of the composite scheme.
[0063] Combining Examples 10 with Examples 11, 12, and 13 and referring to Table 1, it can be seen that: Example 11 (paraffin only) and Example 12 (sodium gluconate only) have limited effects on improving temperature rise and temperature peak. If the effects of the two are linearly superimposed, the expected improvement in temperature control is less than the actual performance of Example 10. However, the actual temperature peak of Example 10 (partitioned loading) occurs much faster than the linear expectation of Examples 11 and 12, proving that there is a positive synergistic effect between paraffin and sodium gluconate. The latent heat storage of paraffin absorbs heat and reduces the temperature peak in the early stage of temperature rise, creating a milder temperature environment for the slow release and condensation of sodium gluconate, making the retarder release more stable and longer. The retarder continuously inhibits the heat release of hydration, which in turn leaves "marginal space" for the subsequent phase change heat storage of paraffin, forming a positive feedback loop. In contrast, the temperature control effect of Example 13 (paraffin and sodium gluconate mixed in the tube, non-partitioned loading) is even worse than that of Example 5 without loading. This is because the two substances compete for the halloysite lumen space, resulting in a serious deficiency in their respective loading and mutual interference in release behavior. Therefore, the partitioned loading design of "paraffin inside the tube + sodium gluconate outside the tube" cleverly utilizes the difference in charge characteristics between the positively charged inner wall and the negatively charged outer wall of halloysite nanotubes, realizing the independent encapsulation and synergistic release of the two functional substances, avoiding competitive adsorption, and producing a true dual synergistic effect of "physical cooling + chemical cooling".
[0064] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A low-heat-of-hydration concrete, characterized in that, Including the following parts by weight of raw materials: 218-225 parts cement; 160-168 parts of fly ash; 118-125 parts of mineral powder; 23-24 parts silica fume; 820-830 parts of graded coarse aggregate; Fine aggregate 850-855 parts; 10-11 parts of slow-release polycarboxylate superplasticizer; 0.03–0.032 parts of air-entraining agent; The water-to-binder ratio is 0.3 to 0.
31.
2. The low heat of hydration concrete according to claim 1, characterized in that, The cement is PO 42.5 ordinary Portland cement; the fly ash is Grade I fly ash; the mineral powder is S95 grade granulated blast furnace slag powder; and the silica fume is dense micro silica fume.
3. The low heat of hydration concrete according to claim 1, characterized in that, The concrete also includes the following raw materials in parts by weight: Halloysite nanotubes, 8–12 parts; 12-16 parts of calcium carbonate whiskers; Polyvinyl alcohol fiber 1.5 to 2 parts.
4. The low heat of hydration concrete according to claim 3, characterized in that, The halloysite nanotubes are loaded with paraffin wax inside the tube lumen and with sodium gluconate loaded on the outer wall.
5. The low heat of hydration concrete according to claim 4, characterized in that, The paraffin loading is 50% of the halloysite nanotube mass.
6. The low heat of hydration concrete according to claim 4, characterized in that, The loading of sodium gluconate is 5% of the mass of halloysite nanotubes.
7. The low heat of hydration concrete according to claim 4, characterized in that, The method for preparing halloysite nanotubes loaded with paraffin and sodium gluconate is as follows: The dried halloysite nanotubes were mixed with molten paraffin and kept under vacuum, allowing the paraffin to enter the lumen of the halloysite nanotubes. Filter and separate, and wash away excess paraffin wax from the surface; Halloysite nanotubes loaded with paraffin are dispersed in an aqueous solution of sodium gluconate and stirred to allow sodium gluconate to be electrostatically adsorbed on the outer wall of the halloysite nanotubes. After filtration, drying, and grinding through a 200-mesh sieve, a composite powder of halloysite nanotubes loaded with paraffin and sodium gluconate is obtained.
8. A method for preparing low-heat-of-hydration concrete according to any one of claims 1 to 7, characterized in that, Includes the following steps: Each raw material is pretreated, mixed in stages, and stirred until homogeneous.